2021
DOI: 10.1146/annurev-pharmtox-030620-104842
|View full text |Cite
|
Sign up to set email alerts
|

Preventing and Treating Anthracycline Cardiotoxicity: New Insights

Abstract: Anthracyclines are the cornerstone of many chemotherapy regimens for a variety of cancers. Unfortunately, their use is limited by a cumulative dose-dependent cardiotoxicity. Despite more than five decades of research, the biological mechanisms underlying anthracycline cardiotoxicity are not completely understood. In this review, we discuss the incidence, risk factors, types, and pathophysiology of anthracycline cardiotoxicity, as well as methods to prevent and treat this condition. We also summarize and discus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
73
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(74 citation statements)
references
References 158 publications
0
73
0
1
Order By: Relevance
“…In a recent review, it was shown that 9% of people receiving anthracycline chemotherapy developed cardiotoxicity, and cardiotoxicity occurred within the first year after the completion of chemotherapy in 98% of cases ( 41 ). Our results were largely in agreement with those data, but with obvious heterogeneity, which was mainly attributed to the different cancer types and corresponding treatment options.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent review, it was shown that 9% of people receiving anthracycline chemotherapy developed cardiotoxicity, and cardiotoxicity occurred within the first year after the completion of chemotherapy in 98% of cases ( 41 ). Our results were largely in agreement with those data, but with obvious heterogeneity, which was mainly attributed to the different cancer types and corresponding treatment options.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, Dox levels were higher in the heart than in the kidney, spleen, and lungs for both the PDC and Dox treated mice. This is likely due to the cardiotoxicity of Dox as it tends to accumulate in the heart [ 41 , 42 ]. Higher levels of Dox in the heart compared to other organs were also observed by others after mice were treated with free Dox [ 43 , 44 , 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…These results show higher specificity of PDC for the tumor tissue with less systemic toxicities compared to free Dox ( Figure 4 b). The usage of Dox is greatly limited by its cardiotoxic effects, ranging from occult changes in myocardial structure to severe cardiomyopathy and heart failure requiring cardiac transplantation [ 41 ]. Of note, the Dox levels in hearts after PDC treatment were much lower (1.4 times) compared to free Dox treatment group.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the exact underlying mechanism of AIC still remains unclear [20], although several hypotheses have been put forward, such as the generation of mitochondrial reactive oxygen species (ROS), disruption of mitochondrial biogenesis, and the induction of ferroptosis [20]. Aside from the cumulative dose, there are some widely known clinical risk factors that play an important role in the development of AIC, i.e., age, gender, hypertension, diabetes and smoking [21].…”
Section: Introductionmentioning
confidence: 99%